2021
DOI: 10.32322/jhsm.899515
|View full text |Cite
|
Sign up to set email alerts
|

A relationship between musculoskeletal pain and prognosis in hospitalized COVID-19 patients

Abstract: Introduction:Musculoskeletal system complaints are often encountered in patients with COVID-19. The aim of this study was to evaluate the frequency of symptoms such as arthralgia, myalgia, and arthritis in hospitalized patients and their relationship with the final prognosis. Material and Method: Complaints related to myalgia, arthralgia, arthritis-like symptoms, laboratory parameters, VAS scores and localized painful areas of 154 hospitalized patients who were treated with a COVID-19 diagnosis were recorded o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Mono-or oligo-articular arthritis was predominat in the lower limbs and not associated with enthesitis or inflammatory back pain as reported by Taha et al [26] . Demirel et al [27] . They studied 154 hospitalized cases, and their observations were reported during the admission period (71.4% and 55.8%, respectively) that is similar to our observation.…”
Section: Discussionmentioning
confidence: 99%
“…Mono-or oligo-articular arthritis was predominat in the lower limbs and not associated with enthesitis or inflammatory back pain as reported by Taha et al [26] . Demirel et al [27] . They studied 154 hospitalized cases, and their observations were reported during the admission period (71.4% and 55.8%, respectively) that is similar to our observation.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with neurological and musculoskeletal pain symptoms in multiple logistic regressionDiscussionIn this study more than half of the patients (66, 53.7%) developed "neurological and musculoskeletal pain symptoms" in the form of headache (43.9%), generalized myalgia (31.8%), and polyarthralgia (25.7%). Demirel et al[28] reported that among 154 COVID-19 hospitalized Turkish patients, 71.4% developed myalgia (71.4%) and 55.8% arthralgia, respectively. Similarly, Jena et al[23] reported pain symptoms among 61.5% of COVID-19 patients.…”
mentioning
confidence: 99%